Effectiveness of entrepreneurship programmes in developing entrepreneurship skills towards quality TVET graduates - Ismail, Affero; Adnan, Wan Nurashida; Masek, Alias; Hassan, Razali; Hashim, Suhaizal; Ismail, Mohd Erfy (Penerbit UTHM, 2019)
Engagement in self-employment has been emphasised by many TVET institutions as one of the employability criterion in determining the quality of TVET graduates. Series of entrepreneurship programmes has been designed to develop student’s skill in strategizing the steps for future plan after graduation, but the impact has not yet been evaluated. Therefore, this study was conducted to investigate the relationship between student’s perception of the effectiveness of entrepreneurship programmes and entrepreneurial skills in a Malaysian Public University. A quantitative survey study was designed using questionnaires. A total of 300 undergraduates’ students were randomly selected as the respondents. The data were analysed using descriptive statistics including frequency, percentage and mean aided by the Statistical Package for Social Sciences (SPSS) 22. The research findings showed that students' perceptions of the effectiveness of entrepreneurship programmes has a positive moderately correlation to students perceived of self-entrepreneurial skills development. Thus, these findings have a significant impact on the implementation of the entrepreneurship programmes organised by the university, especially to students. The implementation of these programmes should be disclosed starting students studying from the first year up to the end of their programmes, so the process is not stalled half way and the students can see their effectiveness. This is necessary to design and implement programmes of entrepreneurship development well in order to allow the number of entrepreneurs among students increases and establish successful entrepreneurs capable of competing at global level.